An open-source quadrature-based population balance solver for OpenFOAM. (2nd February 2018) - Passalacqua, A.; Laurent, F.; Madadi-Kandjani, E.; Heylmun, J.C.; Fox, R.O.
Highlights: Implemented extended quadrature method of moments into OpenFOAM. Robust algorithm ensuring moment realizability. Verification and validation in 0-D aggregation and breakup problems. Validation for aggregation and breakup problem in Taylor-Couette reactor. Abstract: The extended quadrature method of moments (EQMOM) for the solution of population balance equations (PBE) is implemented in the open-source computational fluid dynamic (CFD) toolbox OpenFOAM as part of the OpenQBMM project. The moment inversion procedure was designed (Nguyen et al., 2016) to maximize the number of conserved moments in the transported moment set. The algorithm is implemented in a general structure to allow the addition of other kernel density functions defined on R +, and arbitrary kernels to describe physical phenomena involved in the evolution of the number density function. The implementation is verified with a set of zero-dimensional cases involving aggregation and breakage problems. Comparison to the rigorous solution of the PBE provides validation for these cases. The coupling of the EQMOM procedure with a CFD solver to address aggregation and breakage problems of non-inertial particles is validated against experimental measurements in a Taylor-Couette reactor from the literature.